Coaching of Writing Students’ Thesis: The Implementation of Community Service - Connie, Connie; Kristiawan, Muhammad; Asvio, Nova; Sriyanti, Echa (Graduate Program Magister Manajemen Pendidikan, 2024)
Learning to write a thesis is not only about getting a degree, but also about developing valuable skills and knowledge for an academic and professional future. Thesis allows students to develop their research skills. They learn about research methodology, data analysis, and constructing strong arguments. Writing a thesis requires a deep understanding of the chosen topic. This encourages students to become experts in their field of study. This service is in the form of training for students that aims to provide them with provisions to be able to write a good thesis. The service method used is presentation and discussion, where participants listen to presentations from speakers and then continue with discussions. Participants who take part in this service are students of STIESNU Bengkulu. The results of this service are expected that participants will be able to write a good thesis. This training has a major impact on improving the abilities of participants, namely students, in writing a thesis. The abilities of the participants have improved in writing a thesis, both in terms of presenting an interesting introduction, presenting a systematic literature review, being able to determine the right research method to answer the formulation of problems and research objectives, being able to present research results and compile relevant discussions, interpretations and implementations, and being able to make relevant conclusions and recommendations to users and further researchers.